Teologi Islam di Era Modern: Antara Tantangan dan Peluang dalam Pemikiran Kontemporer - Rusli, Muh (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
The study of Islamic theology experiences various challenges amidst the demands of the problems faced by society in the modern era. This article aims to examine the challenges and opportunities of Islamic theology which is expected to be able to provide alternative solutions to every problem faced by society. In answering these problems, the method used is qualitative with a content analysis approach. The results show that the solution offered by Islamic theology is not an easy thing because globalization spoils people with various literatures without a filter that is in line and not in line with Islam. in this case, it requires the ability to: (1) examine religious texts with various methods that are relevant to the current context; (2) inclusive and holistic religious education; (3) enrich religious publications and research; (4) collaborate and extensive networks between theologians; and (5) open and inclusive dialogue in every religious problem.